Exploring Sodium Insertions into Delithiated NMC Structures: Toward the Utilization of Recycled Materials in Sodium-Ion Batteries - Krabao, Phongsit; Kaewmala, Songyoot; Limphirat, Wanwisa; Meethong, Nonglak (KKU Science Journal, 2025)
As the demand for sustainable and cost-effective energy storage increases, sodium-ion batteries (SIBs) are gaining attention as a viable alternative to lithium-ion systems, owing to sodium’s abundance and lower cost. In this work, we present an innovative strategy to bridge these technologies by reutilizing NMC cathodes layered transition metal oxides commonly used in lithium-ion batteries as active materials in SIBs. The LiNMC cathodes were delithiated in Li half-cells and subsequently sodiated in Na half-cells to form sodiated Li1-xNMC phases (NayNMC). The electrochemical characteristics of the new sodium phases NayNMC were compared, focusing on the effect of transition metal composition on sodium-ion transport and stabilization of the layered structure. Initial charge capacities were closely related to the lithium ions retained in the structure, which stabilized the O3-type layered structure. The capacities, rate capability, and cycling stability of the NayNMC materials were influenced by the transition metal composition. Notably, NayNMC811 exhibited the best overall performance in terms of usable capacity, rate capability, and cycling stability. These findings reveal how transition metal composition governs structural stability and performance, offering a clear strategy for designing next-generation sodium-ion cathodes from recycled materials.